2004
DOI: 10.1042/bj20031541
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the bioenergetic phenotype of mitochondria is a hallmark of breast, gastric, lung and oesophageal cancer

Abstract: Recent findings indicate that the expression of the beta-catalytic subunit of the mitochondrial H+-ATP synthase (beta-F1-ATPase) is depressed in liver, kidney and colon carcinomas, providing further a bioenergetic signature of cancer that is associated with patient survival. In the present study, we performed an analysis of mitochondrial and glycolytic protein markers in breast, gastric and prostate adenocarcinomas, and in squamous oesophageal and lung carcinomas. The expression of mitochondrial and glycolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
121
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 24 publications
(26 reference statements)
9
121
1
Order By: Relevance
“…Similarly, genetic manipulation of the levels of PGC1a, a transcription factor whose activity fosters mitochondrial biogenesis, OXPHOS and fatty acid oxidation, revealed that knockout of PGC1a provokes intestinal tumor susceptibility whereas its overexpression hampers colorectal carcinogenesis (D'Errico et al, 2011). Other observations suggest a lower mitochondrial and a higher glycolytic activity: human tumor tissues show lower levels of H þ -ATP synthase, the molecular motor that couples the mitochondrial proton gradient to ATP synthesis, and higher levels of glycolytic enzymes when compared with normal tissue biopsies (Isidoro et al, 2004). In strongly glycolytic anaplastic and papillary thyroid carcinomas, each tumor shows a specific panel of glycolytic gene overexpression (Hebrant, personal communication).…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
“…Similarly, genetic manipulation of the levels of PGC1a, a transcription factor whose activity fosters mitochondrial biogenesis, OXPHOS and fatty acid oxidation, revealed that knockout of PGC1a provokes intestinal tumor susceptibility whereas its overexpression hampers colorectal carcinogenesis (D'Errico et al, 2011). Other observations suggest a lower mitochondrial and a higher glycolytic activity: human tumor tissues show lower levels of H þ -ATP synthase, the molecular motor that couples the mitochondrial proton gradient to ATP synthesis, and higher levels of glycolytic enzymes when compared with normal tissue biopsies (Isidoro et al, 2004). In strongly glycolytic anaplastic and papillary thyroid carcinomas, each tumor shows a specific panel of glycolytic gene overexpression (Hebrant, personal communication).…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
“…These include a higher mitochondrial membrane potential, modulation of the expression of PTPC components and enhanced rates of ATP generation through glycolysis rather than through oxidative phosphorylation (a phenomenon known as the Warburg effect) in cancer cells (Warburg et al, 1930;Pedersen, 1978Pedersen, , 2007aDang and Semenza, 1999;Cuezva et al, 2002;Debatin et al, 2002;Pedersen et al, 2002;Kroemer, 2003Kroemer, , 2006Isidoro et al, 2004;Hay, 2005, 2006;Galuzzi et al, 2006;Mathupala et al, 2006), possibly explaining the selective action of jasmonates on such cells. Indeed, we have found that jasmonates cause significant decreases in cellular ATP levels in cancer, but not in normal cells Goldin et al, 2007;Heyfets and Flescher, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Coded samples were received to protect patient confidentiality after approval of the project by the Institutional Review Board. Tissue sections of paired normal and tumor tissue derived from each patient were processed (25). Details of the clinicopathological features of the patients have been recently provided (see Table 1 in Ref.…”
mentioning
confidence: 99%